PERAN UNIT PELAYANAN PEREMPUAN DAN ANAK (PPA) POLRESTABES BANDUNG DALAM MENANGANI KEKERASAN TERHADAP ANAK DI KOTA BANDUNG - Dara Dhenissa Herman; Yuyun Yuningsih (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
This research is entitled "The role of the Polrestabes Bandung's Women and Children Service Unit in Dealing with Violence Against Children in Bandung". Violence against children is increasing in Indonesia, and the police are at the forefront in dealing with it. The Women and Children Service Unit (PPA) has a big responsibility in maintaining the rule of law, supporting protection efforts, and combating violent crimes against children, as well as providing protection services to victims. The research method used is descriptive with a qualitative approach, using purposive sampling to select informants, and data collection techniques including in-depth interviews, observation, and document study. The results show that the Polrestabes Bandung's Women and Children Service Unit plays an important role in handling violence against children by providing specialized services and protection for victims, Investigation and Criminal Investigation, collaborating and coordinating with various related institutions and agencies. Supporting factors that influence the Polrestabes Bandung's Women and Children Service Unit include forensic evidence, witness statements, and socialization, while inhibiting factors include a lack of trained investigators, victims or perpetrators who lie, and special needs that are difficult for the Polrestabes Bandung's Women and Children Service Unit to address. In addition, social workers also have an important role in handling cases of violence against children as connectors, educators, counselors, or clinicians. This research provides practical and theoretical implications in the field of social welfare.